Antimicrobial peptides - Phoenix, David, 1966-; Dennison, Sarah R.; Harris, Frederick (Research fellow) (Weinheim, Germany : Wiley-VCH Verlag GmbH & Co KCaA, 2013)
In this didactically-written text, the small team of expert authors presents the field in a comprehensive and accessible manner that is well suited for students and junior researchers. The result is a highly readable and systematically structured introduction to antimicrobial peptides, their structure, biological function and mode of action. The authors point the way towards a rational design of this potentially highly effective new class of clinical antibiotics on the brink of industrial application by discussing their design principles, target membranes and structure-activity relationship.
Antimicrobial peptides: their history, evolution, and functional promiscuity -- Cationic antimicrobial peptides -- Anionic antimicrobial peptides -- Graphical techniques to visualize the amphiphilic structures of antimicrobial peptides -- Models for the membrane interactions of antimicrobial peptides -- Selectivity and toxicity of oncolytic antimicrobial peptides.
Includes bibliographical references and index.
Description based on online resource; title from electronic title page (ebrary, viewed on August 31, 2015).
Keywords: Peptide antibiotics; Protein drugs; Peptides -- therapeutic use; Microbial peptides; Anti-Infective Agents -- pharmacology; Antimicrobial Cationic Peptides -- pharmacology; Amino acids -- Analysis; Microbial pesticides; Medicine--Basic Sciences; Pharmacy; Electronic books; Electronic books; Electronic books